TOWARDS ADABIC INTERCULTURAL COMMUNICATION - Che Mahzan Ahmad; Shafizan Mohamed; Aini Maznina A.Manaf (Journal of Islamic, Social, Economics and Development, 2020)
The Islamic communication can be seen and studied through the teachings of theQuran and the exemplary practices of the prophet Muhammad S.A.W. Unfortunately it is yetto be noticed nor accepted mainly because of how Muslim scholars are unable to putcommunication into context and materialize it into a proper scholarly discipline in the waysthat the western scholars have been able to do through their development of models, theories,ideas and even ethics for communication. This article attempts to fill in this gap in the study ofIslamic communication by highlighting an area very relevant in this contemporary time that isintercultural communication. More than simply discussing about it, this article proposes anIslamic model that can expand the study of ICC by offering an alternative that can improveand even complement the existing approaches that are inherently secular and western-centric